Proceedings of the 2014 Recommender Systems Challenge 2014
DOI: 10.1145/2668067.2668072
|View full text |Cite
|
Sign up to set email alerts
|

Predicting User Engagement in Twitter with Collaborative Ranking

Abstract: Collaborative Filtering (CF) is a core component of popular web-based services such as Amazon, YouTube, Netflix, and Twitter. Most applications use CF to recommend a small set of items to the user. For instance, YouTube presents to a user a list of top-n videos she would likely watch next based on her rating and viewing history. Current methods of CF evaluation have been focused on assessing the quality of a predicted rating or the ranking performance for top-n recommended items. However, restricting the recom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…GBT have shown to outperform other models in classification and regression tasks and have been used successfully for audience engagement prediction [6].…”
Section: Resultsmentioning
confidence: 99%
“…GBT have shown to outperform other models in classification and regression tasks and have been used successfully for audience engagement prediction [6].…”
Section: Resultsmentioning
confidence: 99%
“…The third type of approach (c), adopted by the web-analytics community, has been studying user engagement through online behaviour metrics that assess users' depth of engagement within a site, e.g., the time spent on a webpage. Studies on user engagement in the contexts of desktopbased systems [56] and websites [13,65] have shown that simple metrics such as dwell time are meaningful and robust in modelling user engagement. For example, the time spent on a resource has been validated as an effective metric for measuring user engagement in the context of web search [1,3], and recommendation tasks [64].…”
Section: User Engagementsmentioning
confidence: 99%
“…One way user engagement has been measured at a large scale is by tracking how long users spend with content, e.g., the time spent on a webpage. Studies on user engagement in the contexts of desktop-based systems [56] and websites [13,65] have shown that simple metrics such as dwell time are meaningful and robust in modelling user engagement. More importantly, these studies have shown that with an awareness of engagement, users' experience with a system can be substantially improved which in turn leads to user growth, user retention, and increasing revenue streams.…”
Section: Introductionmentioning
confidence: 99%
“…Context-aware recommender systems (CARS) [9,10] improve recommendation quality by incorporating contextual information to the recommendation process -e.g., time [18], location [26], social ties [16], or mood [34] -which enables them to adapt to the specific user's situation. In this work we are particularly interested in emotional context and its impact in CARS.…”
Section: Related Workmentioning
confidence: 99%
“…We incorporate the emotional context into the recommender system by following a Collaborative Ranking (CR) approach [12,16] -other state-of-the-art alternatives for CARS include Factorization Machines [33] and N-dimensional Tensor Factorization [21]. The main idea behind this approach is to cast the recommendation problem into a (personalized) learning-to-rank task [25].…”
Section: Emotion-aware Recommendationmentioning
confidence: 99%